Self-Sacrifice of a Scientist in Soviet-Russian Cinema - S. M. Medvedeva (Vestnik MGIMO-Universiteta)
Abstract: In the article we analyze the evolution of the idea of self-sacrifice of a scientist in Soviet-Russian cinema (from 1930th until now). The research is based on Weber-Merton’s assumption that the development of modern science stemmed from religion. And in this sense scientific work could be regarded as a kind of religious activity. As a result a number of traits (more typical for a priest) were attributed to a scientist. Such traits are the following: self-sacrifice (in the name of science), asceticism, deep devotion to ideals, etc. As it is shown in the article these pseudoreligious traits remain unchanged in the cinematographic images of scientists. In the article we ague, that the subject of self-sacrifice of a scientist was pictured by Soviet-Russian cinema during its whole history. This ability to self-sacrifice serves as a criterion to prove that a scientist is a true scientist. Nevertheless, it is possible to separate out three periods of picturing of self-sacrifice according to implicit sense of action: 1) period of Stalin’s cinema (1930th-1950th); 2) period of Thaw and Stagnation (1960th-1980th); 3) postsoviet cinema (until now). Each period has its unique tradition of presentation of self-sacrifice of a scientist. Finally we ague, that in the late soviet time appeared a trend to show the sacrifice in the name of science as a senseless and useless action. Scientists in the cinema either lost their ability to self-sacrifice or they sacrificed in vain. In post soviet cinema such tragic attitudes increased: now a scientist has to sacrifice himself on purpose to give up science. It means that science doesn’t worth sacrifice any more. This tendency reveal deep moral crisis among modern Russian intelligentsia.